MEMBEBASKAN ANAK TUNADAKSA DALAM MEWUJUDKAN MASYARAKAT MULTIKULTURAL DEMOKRATIS - Fawziah Zahrawati B (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2018)
Crippled is a person who has a physical disability, body, and orthopedic defects. Because of the incompleteness of body functions, they face many obstacles, so they feel there is a crane that alienated in accessing public facilities. This paper will discuss the efforts that can be taken to liberate the children's crippled in order to realize a democratic multicultural society. This crippled liberate should start by: everyone has to change his paradigm about crippled children and must realize that basically every human being has flaws; school readiness in accepting crippled children should be noted; and provide special facilities for crippled people. Thus the crippled children can still socialize with the general public so that they do not feel alienated in accordance with the goals of democratic and multicultural education to realize equality.